An ethnographic study on developing and communicating identity in the Kano Kantin Kwari business community, Nigeria / Hauwa A. M. Salihu - Hauwa , A. M. Salihu (2022)
Most studies on the African communities tend to disregard how identity nowadays supports the need for social make-up reflecting styles embedded in peoples’ practices and structures. However, little attention has been paid to the indigenous business communities found in the African continent, particularly, Nigeria. This study is thus concerned with addressing this research gap from an interdisciplinary perspective using ‘community of practice’ (CoP) and ‘acts of identity’ frameworks to explore how participants develop and communicate identity in the Kano Kantin Kwari business community, Nigeria. Using qualitative linguistic ethnographic methods for data collection and analysis, 5 focus groups and 20 individual participants were selected through a snowball sampling. The findings obtained showed Kantin Kwari’s CoPs through collaboration, networks of role relationships, and social situations. Findings also offered social and pedagogical implications and revealed how the participants develop identity by learning-in-practice and thus identity-in-practice. For the most part, macro influences and micro-practices determined members’ domain and negotiation of their identities by flexibly performing narrated, executed and enacted identities. Likewise, members revealed the significance of sociocultural, socio-historical, and sociopsychological backgrounds in projecting, focusing and diffusing different identities of the ‘DanKwari (individual), ‘YanKwari (group), and multiple identities. Accordingly, members communicated their identities using language, metaphors, and symbols that exposed growing ethnolinguistic identification of Hausaness (ethnicised identity) and ‘languaging’ and unfreezing the legacy affiliated with English as Nigerian lingua franca. Despite the ethnographic fieldworker’s constraints like the ethics, context, rigours, and cultural redefinition that occasionally muddled the entire field, it provided the researcher with a better understanding of the fieldwork basics. This study provides implications for similar under-represented and muffled communities as it reveals how identity as an ongoing phenomenon is socially constructed, developed, practised and communicated.